Impact of sustainability reporting on accounting information quality - Diana Ferreira; Cláudia Pereira; Mário Queirós; Albertina Paula Monteiro (Cogent Business & Management)
While several studies suggest that Corporate Social Responsibility (CSR) enhances transparency and firms’ reputation, contributing to increasing accounting information quality, others find a negative relationship due to hiding earnings management practices. Then, we aim to investigate (1) sustainability reporting and its evolution from 2010 to 2021, (2) the United Nations Sustainable Development Goals (SDGs) more disclosed, and (3) whether sustainability reporting is positively associated with accounting information quality (earnings persistence). An additional goal is to analyse the individual impact of environmental and social dimensions on earnings persistence. For that purpose, we combine the literature review with content analysis to compute indices of SDG reporting and panel data regression analysis to investigate the association between earnings persistence and sustainability reporting for Portuguese-listed firms, from 2010 to 2021. We find low sustainability reporting, however, with an increasing trend. Furthermore, we show that firms report more environmental than social activities. In the former, the most disclosed are the SDG 3, 13, 14, and 7. The latter concerns SDGs 4, 5, 8, and 10. In addition, our results suggest that earnings persistence increases with sustainability reporting, both for environmental and social dimensions. We provide evidence regarding sustainability and SDGs reporting, where regulation is in progress and literature is still scarce. In addition, we contribute by showing that firms engaged with non-financial reporting tend to enhance their information transparency, allowing them to improve stakeholders’ decision-making and achieve firms’ legitimacy.